GPS and GSM-Based Vehicle Tracking System - Muhamad Edham Adha Osman; Hasliza Hassan (Progress in Engineering Application and Technology, 2024)
The ability to monitor and handle physical assets and personal data with some degree of flexibility has recently become crucial. Even though physical transportation systems have made it simpler for people to move, it has also become hazardous in several ways. Therefore, in this study, a real-time vehicle tracking and monitoring system has been suggested. Additionally, a system using the Arduino Uno R3 is being developed, including a global system for mobile (GSM) devices and a global positioning system (GPS) to track the precise and accurate position of the car at any given time. The gadget also has a display that may inform the user of the vehicle’s whereabouts at any time. The system uses an Arduino microcontroller to manage and process the GPS data that has been received, connect to a GSM module, and send the location data to a distant server or monitoring station. As a result, the main processing unit, the Arduino MCU gathers GPS data from the receiver, conducts any necessary computations or data processing, and facilitates connection with the GSM module. The function of GSM is to connect to the cellular network and send the location data that has been processed to a tracking server or cloud-based platform. However, this GSM module does not allow the system to connect to a cellular network due to blockage from the service provider. Real-time tracking is made possible by the tracking server, which receives and retains the data.